Systems thinking in practice : applications of the event analysis of systemic teamwork method /: applications of the event analysis of systemic teamwork method. ([2019]) - Stanton, Neville A (Neville Anthony), 1960-; Salmon, Paul M; Walker, Guy
No abstract available